Analysis of The Application of Accounting Software On MSMEs Going Concern During The Covid-19 Pandemic In Bandar Lampung - Sri Astuti; M Muhayin A Sidik; Irawan Irawan (Cita konsultindo, 2023)
The presence of MSMEs and their ability to survive in the crisis stage responds to economic challenges in Indonesia. This is what makes this industrial sector a mainstay in the wheels of the community's economy. MSMEs in Indonesia absorb a total workforce of 97.2 million and contribute to GDP > 57%, greater than the contribution of large and largest businesses in all Asian countries. (Ina primaana, 2020). The purpose of this research is to analyze the effect of using accounting software on the on going concern of MSMEs during the Covid-19 Pandemic in Bandar Lampung City.The results of this study are very important for MSMEs actors in Bandar Lampung City to take advantage of digital technology, namely by using accounting software in preparing their financial reports. With accounting software, MSMEs can make profit calculations clearly, avoid calculating errors during the process of calculating financial reports, and save costs during the COVID-19 pandemic.The research was conducted using quantitative descriptive analysis using Excel and the results are displayed in the form of tables and figures to facilitate understanding. Quantitative descriptive is a statistical analysis method that aims to provide a description or description of the research subject based on variable data obtained from certain subject groups.